A Unique Grubbing Head Prototype for Environmentally Friendly and Sustainable Stump Removal - Staněk, Luboš; Zvěřina, Ladislav; Ulrich, Radomír; Abramuszkinová Pavlíková, Eva (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2022)
Stumps left behind after the felling of trees represent an important source of renewable energy that could be used for fuel mixtures as a sustainable solution. The subject of this research was to determine the influence of tree species, stump diameter size, and subsoil on the time required for stump processing. Evaluated parameters included the mean time for one stump's processing; the stump processing time based on the stump diameter; different soil types and tree species; and the tree species type (coniferous, broadleaved). The research was conducted in the territory of the Czech Republic in 2020/2021. There were 287 stumps and 6 tree species in total. The stumps were uprooted using a new prototype of grubbing head, developed at Mendel University in Brno, attached as an adapter on the boom of a JCB JS 220 LC excavator with a tracked undercarriage and was controlled remotely from an excavator cab. Research results confirmed that the processing time of one stump depends on the stump diameter (GLM), and the time needed for the processing of one stump increased with an increase in stump diameter in all experimental sites. An equation was suggested to predict the time needed to work on one stump.
Keywords: forest operations; mechanization; sustainable management; stump removal; forest biomass; time efficiency; grubbing head